2011
DOI: 10.1002/nau.20944
|View full text |Cite
|
Sign up to set email alerts
|

Rectal distension: The effect on bladder function

Abstract: Rectal distension alters bladder sensation and in some cases urodynamics diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 18 publications
0
30
0
7
Order By: Relevance
“…21 These results were reproduced in women with LUTS, where rectal distention significantly reduced the filling volume at which participants reported first and strong desire to void compared to those with an undistended rectum. 22 In addition, detrusor overactivity was demonstrated only in those patients with distended rectums. In a study of healthy men, rectal distention was associated with increased posterior urethral pressure, which may lead to obstructive voiding symptoms regardless of prostate size.…”
Section: Discussionmentioning
confidence: 98%
“…21 These results were reproduced in women with LUTS, where rectal distention significantly reduced the filling volume at which participants reported first and strong desire to void compared to those with an undistended rectum. 22 In addition, detrusor overactivity was demonstrated only in those patients with distended rectums. In a study of healthy men, rectal distention was associated with increased posterior urethral pressure, which may lead to obstructive voiding symptoms regardless of prostate size.…”
Section: Discussionmentioning
confidence: 98%
“…This association is justified because constipation is related to repeated pelvic pressure and tension, occurring more often than birth (26) . The rectum and the lower urinary tract are intimately related, as they originate from the same embryonic structure, possess the same peripheral innervation, and the central processing of afferent activity occurs in the same area of the brain (27) . The intimate proximity of these systems suggests that dysfunctions in one of them can influence the other's function, even mechanically (28) .…”
Section: Discussionmentioning
confidence: 99%
“…The intimate proximity of these systems suggests that dysfunctions in one of them can influence the other's function, even mechanically (28) . One study that assessed whether rectal distension influenced the results of a urodynamic test showed that rectal distension can cause detrusor hyperactivity in some women; however, the data were inconclusive and further research is needed (27) . A cohort study conducted six months postpartum showed that chronic constipation was a risk factor for postpartum UI (OR 1.86, CI 95% 1.03 -3.34) (16) .…”
Section: Discussionmentioning
confidence: 99%
“…A close relationship between bladder function and intestinal function has been demonstrated in various animal models [9, 10] and in clinical studies [11, 12]. A urodynamic study by De Wachter et al showed that rectal distention significantly influences the sensation of bladder filling [13], while Panayi et al detected detrusor overactivity when the rectum was distended and not when it was empty [12].…”
Section: Introductionmentioning
confidence: 99%